Penilaian awal alat ukuran keupayaan kognitif umum - Noorashikeen Mohamed; Wan Shahrazad Wan Sulaiman; Fatimah Wati Halim (Penerbit Universiti Kebangsaan Malaysia, 2020)
The objective of this research is to assess the validity and reliability of the general mental ability instrument that was developed based on Western norms. The instrument comprise 153 items obtained from the International Cognitive Ability Resources (ICAR) categorised into three dimension (3D) rotation, abstract reasoning, figural analogies, letter-number series, matrix reasoning and verbal reasoning. Forty-five (45) masters-programme students from the Human and Social Science Faculty at a local university undertook the 1-hour test. Utilising the Winsteps software, the Rasch meaurement analysis comprising summary statistics, unidimensionality and item-person measures were used to test the validity and reliability of the ICAR. The research findings indicated that the ICAR has good psychometric properties that is acceptable as a mesure of general mental ability. Nonetheless, the findings also indicated that the ICAR was difficult relative to the respondents’ ability. As such, improvements and selection of appropriate item-difficulty level are required to portray a more accurate level of the general mental ability in the local context.